The larva of Plectrocnemia renetta Malicky 1975 (Trichoptera, Polycentropodidae), including a discriminatory matrix to the larvae of Plectrocnemia Stephens 1836 species of Greece - Waringer, Johann; Malicky, Hans (Zootaxa, 2019)
This paper describes the previously unknown larva of Plectrocnemia renetta Malicky 1975. Information on the morphology of the final instar larva is given and the most important diagnostic features are illustrated. A preliminary discriminatory matrix for the Greek larvae of Plectrocnemia Stephens 1836 is also provided. Plectrocnemia renetta and P. conspersa conspersa (Curtis 1834) belong to the group where the inner and outer dorsal secondary setae on abdominal segment IX are strongly different in length. These two species can be separated from each other by the arrangement of muscle attachment spots on the head capsule, number and length of setae on abdominal sternum IX, and by distribution patterns. With respect to zoogeography, Plectrocnemia renetta has been reported from Cyprus, Turkey, and from the Greek islands of Ikaria and Samos.